Development of ultralight, tough and hydrophobic polymethylmethacrylate/polyvinylidene fluoride shape memory foams for heat insulation applications. (January 2023) - Shi, Zhanlin; Zhao, Guoqun; Wang, Guilong; Zhang, Lei; Wei, Chao; Chai, Jialong
Graphical abstract: Highlights: The plasticization of polyvinylidene fluoride makes foaming temperature window move down by 20 ℃. Polyvinylidene fluoride microcrystals raise nucleation density by 4.4 times and decrease cell size by more than 50%. Blend foams offer a lower thermal conductivity of 31.6 mW∙K −1 ∙m −1 and a higher compressive modulus of 2.7 MPa. Hydrophobicity, shape memory property and flame retardancy of the blend foams were obviously improved. Abstract: Thermal insulation is vital for achieving efficient thermal management, energy conservation, and emission reduction. However, the existing polymer foams still have some performance limitations and cannot meet the application demands in a wider range of situations. Accordingly, herein, an innovative strategy based on polyvinylidene fluoride (PVDF) melt blending and CO2 microcellular foaming was proposed for the fabrication of lightweight high-performance polymethylmethacrylate (PMMA) foams for heat insulation, and ultralight, tough, and hydrophobic foams with outstanding heat insulation and shape memory performances were successfully prepared. Because of the plasticization of PVDF and nucleation of PVDF microcrystals, the foaming temperature window of PMMA substantially descended, and the cellular structure of PMMA became refined. Blend foams with expansion ratios of 36.2, cell sizes of 15.8 μm, and foam densities of 0.0357 g∙cm −3 were obtained at 130 °C. Due to higher porosity and strong infrared absorption ability of PMMA, the resulting foams exhibited thermal conductivities of less than 32 mW∙m −1 ∙K −1 . Owing to the hydrophobicity and incombustibility of PVDF and its microcrystals, the blend foams demonstrated better hydrophobicities, shape memory properties, and flame retardancies. This study provides an effective way for the green and mass production of high-performance polymer foams with appropriate thermal insulation performances.